GOSAFE - Geriatric Oncology Surgical Assessment and Functional rEcovery after Surgery: early analysis on 977 patients. Issue 2 (March 2020) - ,; Garutti, Anna; Taffurelli, Giovanni; Zattoni, Davide; Tramelli, Paola; Sermonesi, Giacomo; Di Candido, Francesca; Carvello, Michele; Sacchi, Matteo; De Lucia, Francesca; Foppa, Caterina; Plas, Matthijs; et al.
Abstract: Objective: Older patients with cancer value functional outcomes as much as survival, but surgical studies lack functional recovery (FR) data. The value of a standardized frailty assessment has been confirmed, yet it's infrequently utilized due to time restrictions into everyday practice. The multicenter GOSAFE study was designed to (1) evaluate the trajectory of patients' quality of life (QoL) after cancer surgery (2) assess baseline frailty indicators in unselected patients (3) clarify the most relevant tools in predicting FR and clinical outcomes. This is a report of the study design and baseline patient evaluations. Materials & Methods: GOSAFE prospectively collected a baseline multidimensional evaluation before major elective surgery in patients (≥70 years) from 26 international units. Short−/mid−/long-term surgical outcomes were recorded with QoL and FR data. Results: 1003 patients were enrolled in a 26-month span. Complete baseline data were available for 977(97.4%). Median age was 78 years (range 70–94); 52.8% males. 968(99%) lived at home, 51.6% without caregiver. 54.4% had ≥ 3 medications, 5.9% none. Patients were dependent (ADL < 5) in 7.9% of the cases. Frailty was either detected by G8 ≤ 14(68.4%), fTRST ≥ 2(37.4%), TUG > 20 s (5.2%) or ASAIII-IV (48.8%). Major comorbidities (CACI > 6) were detected in 36%; 20.9% of patients had cognitive impairment according to Mini-Cog. Conclusion: The GOSAFE showed that frailty is frequent in older patients undergoing cancer surgery. QoL and FR, for the first time, are going to be primary outcomes of a real-life observational study. The crucial role of frailty assessment is going to be addressed in the ability to predict postoperative outcomes and to correlate with QoL and FR.